Method for regulating and optimizing residual stress of SiCf / Ti3Al composite material
By introducing the Mo interface stress relief layer and the alternately deposited Ti3Al/Ti2AlNb matrix layer into the SiC/Ti3Al composite material, the problem of high residual stress during the composite material forming process is solved, and the stability and application potential of the material are improved.
Patent Information
- Application Number
- CN202411844379.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The high residual stress caused by the difference in the thermal expansion coefficient between the fiber and the matrix during the molding process affects the mechanical properties and service life of the material.
By depositing the Mo interface stress release layer on the SiC fiber surface and alternately depositing the Ti3Al matrix layer and the Ti2AlNb matrix stress release layer, a multi-layer structure is formed to reduce the residual stress of the composite material.
It effectively reduces the residual stress of composite materials, improves the processing and service stability of materials, and enhances its application potential in the aerospace field.
Smart Images

Figure CN119640164A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal matrix composite materials, and specifically relates to a SiC f / Ti3Al composite material residual stress control and optimization method. Background Art
[0002] SiC / Ti3Al composite materials can couple the excellent properties of continuous SiC fibers with the advantages of Ti3Al alloys to obtain composite materials with high specific strength, high specific stiffness, low thermal expansion coefficient, high temperature resistance, fatigue resistance and other properties. They are ideal choices for bolt fasteners, thrust rods, turbine shafts, skins, stiffeners and other materials for hypersonic vehicles, and have become a key new material in the field of aerospace manufacturing.
[0003] Since SiC / Ti3Al composites are usually formed by hot pressing, the difference in thermal expansion coefficients between SiC fibers and Ti3Al matrix will inevitably lead to high residual stress in SiC / Ti3Al composites during their manufacturing process. The existence of residual stress will have a serious impact on the various mechanical properties and service life of the composites, especially during the service life of SiC / Ti3Al composites, the uneven residual stress inside the composites may become the cause of crack initiation and expansion inside the material, and then lead to catastrophic fracture failure of the material.
[0004] It can be seen that the existence of high residual stress is a key factor limiting the application of SiC / Ti3Al composites. Therefore, how to reduce the residual stress in SiC / Ti3Al composites without affecting the performance of the composites has become an urgent problem to be solved. Summary of the invention
[0005] The present invention aims to provide a SiC f / Ti3Al composite material residual stress control and optimization method, the method provided by the present invention can effectively reduce SiC f / Ti3Al composite material internal residual stress, SiC prepared by the control and optimization method of the present invention f / Ti3Al composite materials can be used as a high-performance, low residual stress strategic aerospace material.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a SiC f The residual stress control and optimization method of the Ti3Al composite material comprises the following steps:
[0008] (1) ion cleaning the SiC fiber containing the carbon coating under argon conditions to obtain a pretreated SiC fiber;
[0009] (2) using Mo as a sputtering target, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain a SiC fiber with a Mo interface stress release layer deposited thereon;
[0010] (3) Using Ti3Al alloy and Ti2AlNb alloy as sputtering targets, magnetron sputtering is performed on the SiC fiber deposited with the Mo interface stress release layer under argon conditions, and Ti3Al matrix layer and Ti2AlNb matrix stress release layer are alternately deposited on the surface of the SiC fiber deposited with the Mo interface stress release layer to obtain SiC f / Ti3Al composite precursor wire;
[0011] (4) The precursor wires are evenly arranged and hot isostatically pressed to obtain SiC with residual stress control and optimization. f / Ti3Al composite materials.
[0012] Preferably, the diameter of the SiC fiber containing the carbon coating is 90-110 μm, and the thickness of the carbon coating is 2-4 μm.
[0013] Preferably, the magnetron sputtering parameters in step (2) include: the gas pressure in the coating chamber is 0.6 to 1.2 Pa; the argon gas flow rate is 60 to 100 sccm; the deposition bias is -50 to -300 V; the sputtering current is 0.9 to 2.5 A; the sputtering power is 300 to 600 W; and the deposition rate is 0.8 to 2.4 μm / h.
[0014] Preferably, the Mo interface stress release layer has a thickness of 0.5-3.5 μm.
[0015] Preferably, the magnetron sputtering parameters for the target in step (3) include: argon gas flow rate of 60 to 100 sccm, gas pressure in the coating chamber of 0.5 to 1.1 Pa, deposition bias of -50 to -300 V, sputtering current of 1.6 to 2.4 A, sputtering power of 600 to 800 W, and deposition rate of 2 to 4 μm / h.
[0016] Preferably, the repetition period of the alternate deposition of the Ti3Al matrix layer and the Ti2AlNb matrix stress release layer is ≥3;
[0017] The single layer thickness of the Ti3Al substrate layer is 2-4 μm; the single layer thickness of the Ti2AlNb substrate stress release layer is 0.5-4 μm; and the total thickness of the alternately deposited Ti3Al substrate layer and Ti2AlNb substrate stress release layer is 18-38 μm.
[0018] Preferably, the SiC f In the precursor wire of the SiC / Ti3Al composite material, the total thickness of the SiC fiber surface film layer is 20-40 μm.
[0019] Preferably, the hot isostatic pressing is performed at a temperature of 930 to 980° C., a pressure of 120 to 200 MPa, and a time of 1 to 5 hours.
[0020] The present invention also provides a SiC prepared by the preparation method described in the above technical solution after residual stress regulation and optimization. f / Ti3Al composite material, composed of SiC f / Ti3Al composite precursor wires are uniformly arranged and obtained by hot isostatic pressing; a single SiC f The precursor wire of the SiC / Ti3Al composite material includes SiC fiber, carbon coating, Mo interface stress release layer and alternating Ti3Al matrix layer and Ti2AlNb matrix stress release layer from the inside to the outside.
[0021] The present invention also provides the SiC f Application of Ti3Al / Ti3Al composite materials in aerospace field.
[0022] The present invention provides a SiC f The residual stress control and optimization method of SiC / Ti3Al composite material significantly reduces the residual stress at the interface of the composite material by introducing a Mo interface stress release layer between the continuous SiC fiber and the Ti3Al matrix. The Mo coating is not only a strong stabilizing element of the β-Ti isomorphous type, but also has a moderate thermal expansion coefficient (the thermal expansion coefficient of the Mo coating is between that of the SiC fiber and the Ti3Al matrix). It is introduced into the SiC as an interface stress release layer. f / Ti3Al composites can not only reduce the residual stress induced by the difference in thermal expansion coefficients between the fiber and the matrix at the interface of the composite, but also induce the formation of a β-Ti toughness transition layer at the interface, alleviate the stress concentration at the interface between the continuous SiC fiber and the Ti3Al matrix, and reduce the failure risk of the composite.
[0023] In addition, the stress release layer of Ti2AlNb matrix with high plasticity alternately introduced into the Ti3Al matrix belongs to the same TiAl intermetallic compound as the Ti3Al matrix, and there is a good interface bonding between the two. Compared with Ti3Al, Ti2AlNb has better toughness and can play a good role in releasing residual stress. By constructing Ti3Al / Ti2AlNb matrix multilayers, the residual stress inside the composite material can be effectively reduced while improving the collective toughness.
[0024] The present invention provides a SiCf The residual stress regulation and optimization method of SiC / Ti3Al composite materials aims to effectively reduce the unevenly distributed residual stress in the composite materials by simultaneously regulating and optimizing the residual stress at the interface of the composite materials and in the matrix, thereby improving the processing and service stability of the composite materials and thus improving the application potential of the composite materials. f The application research of / Ti3Al composite materials is of great significance.
[0025] In particular, the present invention is through the above SiC f / Ti3Al composite residual stress control and optimization method can make SiC f The residual stress of the SiC / Ti3Al composite material is effectively reduced, thereby ensuring f The processing and service stability of Ti3Al / Ti3Al composite materials make it possible to be used as a new type of aerospace material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0027] Figure 1 The present invention provides SiC f Residual stress control and optimization method of SiC / Ti3Al composites f Flow chart of / Ti3Al composite materials;
[0028] Figure 2 This is a cross-sectional SEM image of the SiC / Ti3Al composite material obtained in Example 1;
[0029] Figure 3 This is a cross-sectional SEM image of the SiC / Ti3Al composite material obtained in Comparative Example 1;
[0030] Figure 4 This is a cross-sectional SEM image of the SiC / Ti3Al composite material obtained in Comparative Example 3;
[0031] Figure 5 The flow chart of detecting residual stress of SiC / Ti3Al composite material by corrosion method;
[0032] Figure 6 The figure is a comparison diagram of the matrix axial residual stress of the SiC / Ti3Al composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 measured by the corrosion method and the X-ray diffraction method. DETAILED DESCRIPTION
[0033] The present invention provides a SiC f The residual stress control and optimization method of the Ti3Al composite material comprises the following steps:
[0034] (1) ion cleaning the SiC fiber containing the carbon coating under argon conditions to obtain a pretreated SiC fiber;
[0035] (2) using Mo as a sputtering target, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain a SiC fiber with a Mo interface stress release layer deposited;
[0036] (3) Using Ti3Al alloy and Ti2AlNb alloy as sputtering targets, magnetron sputtering is performed on the SiC fiber deposited with the Mo interface stress release layer under argon conditions, and Ti3Al matrix layer and Ti2AlNb matrix stress release layer are alternately deposited on the surface of the SiC fiber deposited with the Mo interface stress release layer to obtain SiC f / Ti3Al composite precursor wire;
[0037] (4) The precursor wires are evenly arranged and hot isostatically pressed to obtain SiC with residual stress control and optimization. f / Ti3Al composite materials.
[0038] In the present invention, unless otherwise specified, all raw materials are commercially available products well known to those skilled in the art.
[0039] The present invention performs ion cleaning on SiC fibers containing carbon coatings under argon conditions to obtain pretreated SiC fibers.
[0040] In the present invention, the diameter of the SiC fiber containing the carbon coating is 90 to 110 μm, and in a specific embodiment, it can be 100 μm; the thickness of the carbon coating can be 2 to 4 μm, and in a specific embodiment, it can be 3 μm; the SiC fiber containing the carbon coating can be a SiC fiber containing a carbon coating and a tungsten core; the diameter of the tungsten core is 14 to 16 μm, and in a specific embodiment, it can be 15 μm.
[0041] In the present invention, the ion cleaning can be performed in the coating chamber of the magnetron sputtering system; the argon gas flow rate of the ion cleaning can be 40-70 sccm, and in a specific embodiment, it can be 60 sccm; the ion source voltage can be 600-900 V, and in a specific embodiment, it can be 800 V; the sample holder rotation speed can be 1-5 r / min, and in a specific embodiment, it can be 3 r / min; the cleaning time can be 10-30 min, and in a specific embodiment, it can be 20 min.
[0042] After obtaining the pretreated SiC fiber, the present invention uses Mo as a sputtering target and performs magnetron sputtering on the pretreated SiC fiber under argon conditions to obtain SiC fiber with a Mo interface stress release layer deposited thereon.
[0043] In the present invention, the magnetron sputtering parameters include: the argon gas flow rate can be 60-100 sccm, and in a specific embodiment, it can be 80 sccm; the gas pressure in the coating chamber can be 0.6-1.2 Pa, and in a specific embodiment, it can be 0.8 Pa or 1 Pa; the deposition bias can be -50--300 V, and in a specific embodiment, it can be -100 V or -200 V; the sputtering current can be 0.9-2.5 A, and in a specific embodiment, it can be 1.5 A or 2 A; the sputtering power can be 300-600 W, and in a specific embodiment, it can be 400 W or 500 W; the deposition rate can be 0.8-2.4 μm / h, and in a specific embodiment, it can be 1 μm / h, 1.5 μm / h or 2 μm / h.
[0044] In the present invention, the thickness of the Mo interface stress release layer may be 0.5-3.5 μm, and in a specific embodiment, may be 1 μm, 2 μm or 3 μm.
[0045] After obtaining the SiC fiber deposited with the Mo interface stress release layer, the present invention uses Ti3Al alloy and Ti2AlNb alloy as sputtering targets, performs magnetron sputtering on the SiC fiber deposited with the Mo interface stress release layer under argon conditions, and alternately deposits Ti3Al matrix layers and Ti2AlNb matrix stress release layers on the surface of the SiC fiber deposited with the Mo interface stress release layer to obtain SiC f / Ti3Al composite pioneer wire.
[0046] In the present invention, the magnetron sputtering parameters include: the argon gas flow rate can be 60-100 sccm, and in a specific embodiment, it can be 80 sccm; the gas pressure in the coating chamber can be 0.5-1.1 Pa, and in a specific embodiment, it can be 0.8 Pa or 1 Pa; the deposition bias can be -50--300 V, and in a specific embodiment, it can be -100 V or -200 V; the sputtering current can be 1.6-2.6 A, and in a specific embodiment, it can be 1.8 A or 2 A; the sputtering power can be 600-1000 W, and in a specific embodiment, it can be 700 W or 800 W; the deposition rate can be 2-4 μm / h, and in a specific embodiment, it can be 3 μm / h or 4 μm / h.
[0047] In the present invention, the repetition period of the alternately deposited Ti3Al substrate layer and the Ti2AlNb substrate stress release layer is ≥3, and in a specific embodiment, it can be 4, 6 or 10; the single layer thickness of the Ti3Al substrate layer is 2 to 4 μm, and in a specific embodiment, it can be 3 μm; the single layer thickness of the Ti2AlNb substrate stress release layer is 0.5 to 4 μm, and in a specific embodiment, it can be 2 μm; the total thickness of the alternately deposited Ti3Al substrate layer and the Ti2AlNb substrate stress release layer is 18 to 38 μm, and in a specific embodiment, it can be 24 μm or 30 μm.
[0048] In the present invention, the SiC f In the precursor wire of the SiC / Ti3Al composite material, the total thickness of the film layer on the surface of the SiC fiber is 20-40 μm, and in a specific embodiment, it can be 26 μm or 32 μm.
[0049] The interface stress release layer, Ti3Al layer and matrix stress release layer on the surface of SiC fiber in the present invention will affect the volume percentage of SiC fiber in the composite material. When preparing the composite material, if the thickness of the interface stress release layer, Ti3Al layer and matrix stress release layer on the surface of SiC fiber is too thin, the gap between SiC fiber and SiC fiber cannot be completely filled, and there will be many holes in the hot-pressed composite material. If the thickness of the interface stress release layer, Ti3Al layer and matrix stress release layer is too thick, the volume percentage of SiC fiber in the composite material will be too small, affecting the mechanical properties of the composite material. The preparation method of SiC / Ti3Al precursor wire provided by the present invention can achieve near-net shaping of composite precursor wire and accurately control the thickness of each layer.
[0050] Obtaining the SiC f After the precursor wire of the / Ti3Al composite material is formed, the precursor wire is evenly arranged and hot isostatic pressing is performed to obtain the SiC f / Ti3Al composite materials.
[0051] In the present invention, the hot pressing also includes cutting and ion beam packaging; the ion beam packaging can be performed in an alloy sleeve; the alloy sleeve is a Ti3Al alloy sleeve.
[0052] In the present invention, the temperature of the hot isostatic pressing can be 930-980°C, and in a specific embodiment, it can be 960°C; the pressure can be 120-200MPa, and in a specific embodiment, it can be 150MPa or 180MPa; the time can be 1-5h, and in a specific embodiment, it can be 2h or 4h.
[0053] The present invention also provides a SiC prepared by the preparation method described in the above technical solution after residual stress regulation and optimization. f / Ti3Al composite material, composed of SiC f / Ti3Al composite precursor wires are uniformly arranged and obtained by hot isostatic pressing; a single SiC f The precursor wire of the SiC / Ti3Al composite material includes SiC fiber, carbon coating, Mo interface stress release layer and alternating Ti3Al matrix layer and Ti2AlNb matrix stress release layer from the inside to the outside.
[0054] The SiC / Ti3Al composite material provided by the present invention has low residual stress and can improve the processing and service stability of the composite material, thereby improving the application potential of the composite material, which is of great significance to the application research of the SiC / Ti3Al composite material.
[0055] The present invention also provides the SiC f / Ti3Al composite materials can be used in the aerospace field.
[0056] In the present invention, the aerospace field includes aerospace engine materials, hypersonic spacecraft materials or aerospace launch vehicle materials; the present invention does not have any special limitation on the application process of the SiC / Ti3Al precursor wire or SiC / Ti3Al composite material in the aerospace field, and the method familiar to those skilled in the art can be adopted.
[0057] In order to further illustrate the present invention, the SiC / Ti3Al precursor wire, composite material, preparation method and application thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0058] Figure 1 The present invention provides SiC f Residual stress control and optimization method of SiC / Ti3Al composites f Flow chart of / Ti3Al composite material, and the specific steps are shown in Examples 1 to 3.
[0059] Example 1
[0060] The SiC provided by the present invention f Residual stress control and optimization method of SiC / Ti3Al composites f / Ti3Al composite material, SiC fiber diameter is 100μm, carbon coating thickness is 2μm, Mo coating thickness at the interface is 2μm, Ti2AlNb coating thickness in the matrix is 2μm, Ti3Al coating thickness is 2μm, and co-deposition is 6 cycles. The specific steps are as follows:
[0061] (1) Cleaning: After placing the Mo target, Ti3Al target, Ti2AlNb target and SiC fiber in the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber should be less than 6×10 -4 Pa, turn on the sample holder rotation switch, the rotation rate is 3r / min, introduce argon gas with a flow rate of 60sccm, and control the pressure in the coating chamber at 0.8Pa. Turn on the ion source power supply, the initial voltage is about 200V, then reduce the argon gas flow rate to make the ion source voltage become 800V, clean for 20min, turn off the ion source, and complete the cleaning.
[0062] (2) Mo interface layer preparation: The target material used is Mo metal target, and the target surface is clean and pollution-free. The vacuum degree in the coating room is less than 6×10 -4 Pa, keep the argon flow rate at 60 sccm, and control the gas pressure in the coating chamber to 0.8 Pa. The deposition bias voltage is -100 V. Turn on the DC power supply of the Mo target to sputter the target, the sputtering current is 1.5 A, the sputtering power is 600 W, and a 2 μm Mo coating is deposited on the surface of the SiC fiber.
[0063] (3) Preparation of stress release layer of Ti3Al substrate and Ti2AlNb substrate: The targets used are Ti3Al alloy target and Ti2AlNb alloy target. The two targets are placed in different target positions, and the target surfaces are clean and free of pollution. The argon gas flow rate is kept constant at 60sccm, and the gas pressure in the coating chamber is controlled at 0.8Pa. The deposition bias is maintained at -100V. The DC power supplies of the Ti3Al target and the Ti2AlNb target are turned on respectively for target sputtering. During the deposition of the Ti3Al layer, the sputtering current is 1.9A and the sputtering power is 700W; during the deposition of the Ti2AlNb layer, the sputtering current is 2A and the sputtering power is 750W. The sample holder rotation speed was controlled at 3 r / min, and a 2 μm thick Ti3Al layer and a 2 μm thick Ti2AlNb layer were alternately deposited on the surface of the SiC fiber. The thickness ratio of the Ti3Al layer to the Ti2AlNb layer was 1:1. The deposition was repeated for 6 cycles to obtain a precursor wire with an interface stress release layer and a matrix stress release layer.
[0064] (4) Preparation of composite materials: The cut precursor wires are arranged tightly and evenly, placed in a Ti3Al alloy sleeve for ion beam packaging, and then the prefabricated sample is hot isostatically pressed at 960℃ / 150MPa for 2h to form. After the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace to obtain SiC f / C / Mo / (Ti3Al / Ti2AlNb)6 composite material.
[0065] Figure 2The cross-sectional SEM image of the SiC / Ti3Al composite material obtained in this embodiment is shown in FIG. Figure 2 It can be seen that the present embodiment successfully prepared a SiC / Ti3Al composite material having a Mo interface stress release layer and a Ti2AlNb matrix stress release layer.
[0066] Example 2
[0067] The SiC provided by the present invention f Residual stress control and optimization method of SiC / Ti3Al composites f / Ti3Al composite material, SiC fiber diameter is 100μm, carbon coating thickness is 2μm, Mo coating thickness at the interface is 2μm, Ti2AlNb coating thickness in the matrix is 2μm, Ti3Al coating thickness is 4μm, and co-deposition is 4 cycles. The specific steps are as follows:
[0068] (1) Cleaning: After placing the Mo target, Ti3Al target, Ti2AlNb target and SiC fiber in the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber should be less than 6×10 -4 Pa, turn on the sample holder rotation switch, the rotation rate is 3r / min, introduce argon gas with a flow rate of 60sccm, and control the pressure in the coating chamber at 0.8Pa. Turn on the ion source power supply, the initial voltage is about 200V, then reduce the argon gas flow rate to make the ion source voltage become 800V, clean for 20min, turn off the ion source, and complete the cleaning.
[0069] (2) Mo interface layer preparation: The target material used is Mo metal target, and the target surface is clean and pollution-free. The vacuum degree in the coating room is less than 6×10 -4 Pa, keep the argon flow rate at 60 sccm, and control the gas pressure in the coating chamber to 0.8 Pa. The deposition bias voltage is -100 V. Turn on the DC power supply of the Mo target to sputter the target, the sputtering current is 1.5 A, the sputtering power is 600 W, and a 2 μm Mo coating is deposited on the surface of the SiC fiber.
[0070] (3) Preparation of stress release layer of Ti3Al substrate and Ti2AlNb substrate: The targets used are Ti3Al alloy target and Ti2AlNb alloy target. The two targets are placed in different target positions, and the target surfaces are clean and free of pollution. The argon gas flow rate is kept constant at 60sccm, and the gas pressure in the coating chamber is controlled at 0.8Pa. The deposition bias is maintained at -100V. The DC power supplies of the Ti3Al target and the Ti2AlNb target are turned on respectively for target sputtering. During the deposition of the Ti3Al layer, the sputtering current is 1.9A and the sputtering power is 700W; during the deposition of the Ti2AlNb layer, the sputtering current is 2A and the sputtering power is 750W. The sample holder rotation speed was controlled at 3 r / min, and a 4 μm thick Ti3Al layer and a 2 μm thick Ti2AlNb layer were alternately deposited on the surface of the SiC fiber. The thickness ratio of the Ti3Al layer to the Ti2AlNb layer was 2:1. The deposition was repeated for 4 cycles to obtain a precursor wire with an interface stress release layer and a matrix stress release layer.
[0071] (4) Preparation of composite materials: The cut precursor wires are arranged tightly and evenly, placed in a Ti3Al alloy sleeve for ion beam packaging, and then the prefabricated sample is hot isostatically pressed at 960℃ / 150MPa for 2h to form. After the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace to obtain SiC f / C / Mo / (Ti3Al / Ti2AlNb)4 composite material.
[0072] Example 3
[0073] The SiC provided by the present invention f Residual stress control and optimization method of SiC / Ti3Al composites f / Ti3Al composite material, SiC fiber diameter is 100μm, carbon coating thickness is 2μm, Mo coating thickness at the interface is 2μm, Ti2AlNb coating thickness in the matrix is 2μm, Ti3Al coating thickness is 6μm, co-deposition is 3 cycles. The specific steps are as follows:
[0074] (1) Cleaning: After placing the Mo target, Ti3Al target, Ti2AlNb target and SiC fiber in the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber should be less than 6×10 -4 Pa, turn on the sample holder rotation switch, the rotation rate is 3r / min, introduce argon gas with a flow rate of 60sccm, and control the pressure in the coating chamber at 0.8Pa. Turn on the ion source power supply, the initial voltage is about 200V, then reduce the argon gas flow rate to make the ion source voltage become 800V, clean for 20min, turn off the ion source, and complete the cleaning.
[0075] (2) Mo interface layer preparation: The target material used is Mo metal target, and the target surface is clean and pollution-free. The vacuum degree in the coating room is less than 6×10 -4 Pa, keep the argon flow rate at 60 sccm, and control the gas pressure in the coating chamber to 0.8 Pa. The deposition bias voltage is -100 V. Turn on the DC power supply of the Mo target to sputter the target, the sputtering current is 1.5 A, the sputtering power is 600 W, and a 2 μm Mo coating is deposited on the surface of the SiC fiber.
[0076] (3) Preparation of stress release layer of Ti3Al substrate and Ti2AlNb substrate: The targets used are Ti3Al alloy target and Ti2AlNb alloy target. The two targets are placed in different target positions, and the target surfaces are clean and free of pollution. The argon gas flow rate is kept constant at 60sccm, and the gas pressure in the coating chamber is controlled at 0.8Pa. The deposition bias is maintained at -100V. The DC power supplies of the Ti3Al target and the Ti2AlNb target are turned on respectively for target sputtering. During the deposition of the Ti3Al layer, the sputtering current is 1.9A and the sputtering power is 700W; during the deposition of the Ti2AlNb layer, the sputtering current is 2A and the sputtering power is 750W. The sample holder rotation speed was controlled at 3 r / min, and a 6 μm thick Ti3Al layer and a 2 μm thick Ti2AlNb layer were alternately deposited on the surface of the SiC fiber. The thickness ratio of the Ti3Al layer to the Ti2AlNb layer was 3:1. The deposition was repeated for 3 cycles to obtain a precursor wire with an interface stress release layer and a matrix stress release layer.
[0077] (4) Preparation of composite materials: The cut precursor wires are arranged tightly and evenly, placed in a Ti3Al alloy sleeve for ion beam packaging, and then the prefabricated sample is hot isostatically pressed at 960℃ / 150MPa for 2h to form. After the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace to obtain SiC f / C / Mo / (Ti3Al / Ti2AlNb)3 composite material.
[0078] Comparative Example 1
[0079] In this comparative example, there is no interface stress release layer and substrate stress release layer, and the thickness of the Ti3Al layer is 24 μm. The specific preparation steps are as follows:
[0080] (1) Cleaning: After placing the Mo target, Ti3Al target, Ti2AlNb target and SiC fiber in the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber should be less than 6×10 -4Pa, turn on the sample holder rotation switch, the rotation rate is 3r / min, introduce argon gas with a flow rate of 60sccm, and control the pressure in the coating chamber at 0.8Pa. Turn on the ion source power supply, the initial voltage is about 200V, then reduce the argon gas flow rate to make the ion source voltage become 800V, clean for 20min, turn off the ion source, and complete the cleaning.
[0081] (2) Preparation of precursor wire: The target material used is Ti3Al alloy target material, and the target surface is clean and free of pollution. The argon gas flow rate is kept constant at 60sccm, and the gas pressure in the coating chamber is controlled at 0.8Pa. The deposition bias voltage is -100V. Turn on the DC power supply of the Ti3Al target to sputter the target, the sputtering current is 1.9A, the sputtering power is 700W, and the sample holder speed is controlled to 3r / min. A 24μm thick Ti3Al coating is alternately deposited on the surface of the SiC fiber to obtain SiC f / Ti3Al composites.
[0082] (3) Composite material preparation: The cut precursor wires are arranged tightly and evenly, placed in a Ti3Al alloy sleeve for ion beam packaging, and then the prefabricated sample is hot isostatically pressed at 960℃ / 150MPa for 2h to form. After the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace to obtain SiC f / C / Ti3Al composite materials.
[0083] Figure 3 The cross-sectional SEM image of the SiC / Ti3Al composite material obtained in this embodiment is shown in FIG. Figure 3 It can be seen that the comparative example prepared a SiC / Ti3Al composite material containing neither a Mo interface stress release layer nor a Ti2AlNb matrix stress release layer.
[0084] Comparative Example 2
[0085] In this comparative example, the interface stress release layer is a Cr layer with a thickness of 2 μm, there is no substrate stress release layer, and the thickness of the Ti3Al layer is 24 μm. The specific preparation steps are as follows:
[0086] (1) Cleaning: After placing the Cr target, Ti3Al target, Ti2AlNb target and SiC fiber in the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber should be less than 6×10 -4 Pa, turn on the sample holder rotation switch, the rotation rate is 3r / min, introduce argon gas with a flow rate of 60sccm, and control the pressure in the coating chamber at 0.8Pa. Turn on the ion source power supply, the initial voltage is about 200V, then reduce the argon gas flow rate to make the ion source voltage become 800V, clean for 20min, turn off the ion source, and complete the cleaning.
[0087] (2) Preparation of Cr interface layer: The target material used is Cr metal target, and the target surface is clean and pollution-free. The vacuum degree in the coating room is less than 6×10 -4 Pa, keep the argon flow rate at 60sccm, and control the gas pressure in the coating chamber to 0.8Pa. The deposition bias voltage is -100V. Turn on the DC power supply of the Cr target to sputter the target, the sputtering current is 1.5A, the sputtering power is 600W, and a 2μm Cr coating is deposited on the surface of the SiC fiber.
[0088] (3) Preparation of precursor wire: The target material used is Ti3Al alloy target material, and the target surface is clean and free of pollution. The argon gas flow rate is kept constant at 60sccm, and the gas pressure in the coating chamber is controlled at 0.8Pa. The deposition bias is kept at -100V. The DC power supply of the Ti3Al target is turned on to sputter the target. The sputtering current is 1.9A, the sputtering power is 700W, and the sample holder speed is controlled at 3r / min. A 24μm thick Ti3Al coating is alternately deposited on the surface of the SiC fiber to obtain SiC f / Ti3Al composites.
[0089] (4) Preparation of composite materials: The cut precursor wires are arranged tightly and evenly, placed in a Ti3Al alloy sleeve for ion beam packaging, and then the prefabricated sample is hot isostatically pressed at 960℃ / 150MPa for 2h to form. After the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace to obtain SiC f / C / Cr / Ti3Al composite materials.
[0090] Comparative Example 3
[0091] In this comparative example, there is no substrate stress release layer, and the thickness of the Ti3Al layer is 24 μm. The specific preparation steps are as follows:
[0092] (1) Cleaning: After placing the Mo target, Ti3Al target, Ti2AlNb target and SiC fiber in the designated position in the coating chamber of the multi-target magnetron sputtering system, the vacuum degree in the coating chamber should be less than 6×10 -4 Pa, turn on the sample holder rotation switch, the rotation rate is 3r / min, introduce argon gas with a flow rate of 60sccm, and control the pressure in the coating chamber at 0.8Pa. Turn on the ion source power supply, the initial voltage is about 200V, then reduce the argon gas flow rate to make the ion source voltage become 800V, clean for 20min, turn off the ion source, and complete the cleaning.
[0093] (2) Mo interface layer preparation: The target material used is Mo metal target, and the target surface is clean and pollution-free. The vacuum degree in the coating room is less than 6×10 -4Pa, keep the argon flow rate at 60 sccm, and control the gas pressure in the coating chamber to 0.8 Pa. The deposition bias voltage is -100 V. Turn on the DC power supply of the Mo target to sputter the target, the sputtering current is 1.5 A, the sputtering power is 600 W, and a 2 μm Mo coating is deposited on the surface of the SiC fiber.
[0094] (3) Preparation of precursor wire: The target material used is Ti3Al alloy target material, and the target surface is clean and free of pollution. The argon gas flow rate is kept constant at 60sccm, and the gas pressure in the coating chamber is controlled at 0.8Pa. The deposition bias is kept at -100V. The DC power supply of the Ti3Al target is turned on to sputter the target. The sputtering current is 1.9A, the sputtering power is 700W, and the sample holder speed is controlled at 3r / min. A 24μm thick Ti3Al coating is alternately deposited on the surface of the SiC fiber to obtain SiC f / Ti3Al composites.
[0095] (4) Preparation of composite materials: The cut precursor wires are arranged tightly and evenly, placed in a Ti3Al alloy sleeve for ion beam packaging, and then the prefabricated sample is hot isostatically pressed at 960℃ / 150MPa for 2h to form. After the hot isostatic pressing is completed, the sample is cooled to room temperature with the furnace to obtain SiC f / C / Mo / Ti3Al composite materials.
[0096] Figure 4 The cross-sectional SEM image of the SiC / Ti3Al composite material obtained in this embodiment is shown in FIG. Figure 4 It can be seen that the comparative example prepared a SiC / Ti3Al composite material with a Mo interface stress release layer.
[0097] Test Example 1
[0098] The residual stress of the SiC / Ti3Al composite matrix of Examples 1 to 3 and Comparative Examples 1 to 3 was tested by corrosion method. The test process is as follows: Figure 5 As shown, the specific steps are as follows:
[0099] 1. Slice and polish the SiC / Ti3Al composite material with a slice thickness of 2 to 3 mm;
[0100] 2. Cut grooves on the polished composite material, and the groove depth is determined by the corrosion depth. After cutting grooves, the polished surface of the composite material is laser marked, and the selected marking points are located on both sides of the grooves;
[0101] 3. Record the fiber height difference near the marking points on both sides;
[0102] 4. Protect one side of the composite material after the groove is cut and then perform corrosion treatment on it;
[0103] 5. After the corrosion is completed, record the fiber height difference near the marking points on both sides again;
[0104] 6. The residual stress of the composite material can be calculated using the following formula.
[0105] When the corrosion method is used to analyze the residual stress of the composite material, the corrosion depth of the SiC fiber is set to l, and the fiber growth after corrosion is Δ, then the axial strain of the fiber is:
[0106]
[0107] The stress of the fiber in the axial direction can be expressed as:
[0108]
[0109] The elastic modulus E of the composite material along the axial direction c Calculated by the law of mixture:
[0110] E c =V f E f +(1-V f )E m
[0111] The stress of the matrix alloy in the axial direction can be obtained by the following formula:
[0112]
[0113] Where V f is the fiber volume percentage, ν is the fiber Poisson's ratio, E f is the fiber elastic modulus, E m is the matrix elastic modulus.
[0114] The test results of residual stress of SiC / Ti3Al composite matrix by corrosion method are shown in Figure 6 .
[0115] Test Example 2
[0116] The residual stress of the SiC / Ti3Al composite matrix of Examples 1 to 3 and Comparative Examples 1 to 3 was detected by X-ray diffraction. The detection process is as follows: Figure 5 As shown, the specific steps are as follows:
[0117] 1. Select the high-angle diffraction peak and The measurements were performed at different ψ angles at three angles of 45° and 90°;
[0118] 2. Calculate separately The interplanar spacing d of the selected crystal planes corresponding to different ψ angles at three angles of 45° and 90°;
[0119] 3. Yes Make a scatter plot and perform linear fitting to get Slope at 45° and 90°
[0120] 4. Obtain the intercept of the fitted line after linear fitting And The average value is d(average,ψ=0).
[0121] 5. The residual stress of the composite material can be calculated using the following formula:
[0122]
[0123] The X-ray diffraction method was used to test the residual stress of SiC / Ti3Al composite matrix. Figure 6 .
[0124] Depend on Figure 6 It can be seen that the SiC / Ti3Al composite material obtained by using the SiC / Ti3Al precursor wire provided by the present invention can realize residual stress regulation and optimization, and effectively reduce residual stress. The reduction of residual stress can improve the processing and service stability of the composite material, thereby improving the application potential of the composite material. It can be seen that the present invention is of great significance to the application research of SiC / Ti3Al composite materials.
[0125] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A SiC f / Ti3Al composite material residual stress control and optimization method, characterized in that: The following steps are involved: (1) ion cleaning the SiC fiber containing the carbon coating under argon conditions to obtain a pretreated SiC fiber; (2) using Mo as a sputtering target, magnetron sputtering the pretreated SiC fiber under argon conditions to obtain a SiC fiber with a Mo interface stress release layer deposited thereon; (3) Using Ti3Al alloy and Ti2AlNb alloy as sputtering targets, magnetron sputtering is performed on the SiC fiber deposited with the Mo interface stress release layer under argon conditions, and Ti3Al matrix layer and Ti2AlNb matrix stress release layer are alternately deposited on the surface of the SiC fiber deposited with the Mo interface stress release layer to obtain SiC f / Ti3Al composite precursor wire; (4) The precursor wires are evenly arranged and hot isostatically pressed to obtain SiC with residual stress control and optimization. f / Ti3Al composite materials.
2. The preparation method according to claim 1, characterized in that: The diameter of the SiC fiber containing the carbon coating is 90-110 μm, and the thickness of the carbon coating is 2-4 μm.
3. The preparation method according to claim 1, characterized in that: The magnetron sputtering parameters in step (2) include: the gas pressure in the coating chamber is 0.6 to 1.2 Pa; the argon gas flow rate is 60 to 100 sccm; the deposition bias is -50 to -300 V; the sputtering current is 0.9 to 2.5 A; the sputtering power is 300 to 600 W; and the deposition rate is 0.8 to 2.4 μm / h.
4. The preparation method according to claim 1 or 3, characterized in that: The thickness of the Mo interface stress release layer is 0.5-3.5 μm.
5. The preparation method according to claim 1, characterized in that: The magnetron sputtering parameters for the target in step (3) include: argon gas flow rate of 60 to 100 sccm, gas pressure in the coating chamber of 0.5 to 1.1 Pa, deposition bias of -50 to -300 V, sputtering current of 1.6 to 2.4 A, sputtering power of 600 to 800 W, and deposition rate of 2 to 4 μm / h.
6. The preparation method according to claim 1 or 5, characterized in that: The repetition period of the alternate deposition of the Ti3Al substrate layer and the Ti2AlNb substrate stress release layer is ≥3; The single layer thickness of the Ti3Al substrate layer is 2-4 μm; the single layer thickness of the Ti2AlNb substrate stress release layer is 0.5-4 μm; and the total thickness of the alternately deposited Ti3Al substrate layer and Ti2AlNb substrate stress release layer is 18-38 μm.
7. The preparation method according to claim 1, characterized in that: The SiC f In the precursor wire of the SiC / Ti3Al composite material, the total thickness of the SiC fiber surface film layer is 20-40 μm.
8. The preparation method according to claim 1, characterized in that: The hot isostatic pressing process is performed at a temperature of 930 to 980° C., a pressure of 120 to 200 MPa, and a time of 1 to 5 hours.
9. SiC prepared by the preparation method according to any one of claims 1 to 8 after residual stress control and optimization f / Ti3Al composite material, characterized in that SiC f / Ti3Al composite precursor wires are uniformly arranged and obtained by hot isostatic pressing; a single SiC f The precursor wire of the SiC / Ti3Al composite material includes SiC fiber, carbon coating, Mo interface stress release layer and alternating Ti3Al matrix layer and Ti2AlNb matrix stress release layer from the inside to the outside.
10. The SiC after residual stress control and optimization according to claim 9 f Application of Ti3Al / Ti3Al composite materials in aerospace field.
Citation Information
Patent Citations
Design method for reducing stress concentration of SiC fiber reinforced titanium-based composite rod-like tensile sample
CN117542457A
High-toughness fiber-reinforced TiAl / Ti3Al multilayer composite material as well as preparation method and application thereof
CN118422142A
Composite materials comprise ceramic or carbon fibers with a metal coating which are embedded in metal matrix whose melting point is lower than that of coating
DE102006040120B3
Manufacture of metallic composite material making use of liquid phase sintering
JP2001011593A
Method of producing titanium composite parts by means of casting and parts thus
US20070068603A1